POSITIVE FEATURES OF THE RELATIONSHIP OF TOLERANCE IN EARLY ADOLESCENCE (American Journal of Research in Humanities and Social Sciences, 2023)
In this article, the positive characteristics of tolerance relations in the period of early adolescence, and the shift in self-awareness are clearly visible in adolescents.